Tackling Unwanted Proteolysis in Plant Production Hosts Used for Molecular Farming - Mandal, Manoj K.; Ahvari, Houtan; Schillberg, Stefan; Schiermeyer, Andreas (Frontiers in Plant Science, 2016)
Although the field of molecular farming has significantly matured over the last years, some obstacles still need to be resolved. A major limiting factor for a broader application of plant hosts for the production of valuable recombinant proteins is the low yield of intact recombinant proteins. These low yields are at least in part due to the action of endogenous plant proteases on the foreign recombinant proteins. This mini review will present the current knowledge of the proteolytic enzymes involved in the degradation of different target proteins and strategies that are applied to suppress undesirable proteolytic activities in order to safeguard recombinant proteins during the production process.